A Smart Approach to Provide the Women Safety by Using Smart Security Devices - Umamaheswari, K. M. (International Journal of Psychosocial Rehabilitation, 2020)
Presently a-days women face a few issues upheld for their uncertainties. The apparatus that is arranged has capacity to follow scopes and longitudes of them and can send content to the close by police control rooms and can likewise the output enlisted numbers. This tireless isn't exclusively utilities for cases like inappropriate activities and rebels doing eve prodding anyway this furthermore help them from any obviousness or any unfitness like dropping down out of nowhere. Worldwide situating framework assists with following the position of the affected injured individual and to send instant messages, the spot and poisonings of the unfortunate casualty to the close by police headquarters and furthermore the contact quantities of the family members of the person in question. This encourages ladies to beat stress and can do the things what they like to do.